Implementation of the Piercing the Corporate Veil Principle in the Liability of Public Limited Companies for Capital Market Conduct Causing Losses to Public Shareholders - Liana Suryani Ali Liana; Hulman Panjaitan; Paltiada Saragi (Inovasi Pratama Internasional. Ltd, 2027)
A Public Limited Company (PT Tbk), as an issuer in the capital market, is obligated to conduct its business activities in accordance with the principles of transparency, accountability, and investor protection. However, in practice, various actions in the capital market may adversely affect public shareholders, including capital market crimes such as fraud, market manipulation, price manipulation, and insider trading, as well as administrative violations that may ultimately result in forced delisting. These circumstances place public shareholders in a vulnerable position due to their limited ability to influence corporate policies through the General Meeting of Shareholders. This study aims to analyze the forms of actions committed by Public Limited Companies that may harm public shareholders and to examine the implementation of the piercing the corporate veil doctrine in establishing the liability of Public Limited Companies for such actions. This study employs a normative juridical research method by examining statutory regulations, legal doctrines, and relevant literature concerning corporate law and capital market law. The research focuses on analyzing actions undertaken by Public Limited Companies that have the potential to harm public shareholders and the implementation of the piercing the corporate veil doctrine in assigning liability for such losses. The findings reveal that actions by Public Limited Companies that may harm public shareholders can be classified into three main categories: capital market crimes, administrative violations, and unlawful acts (torts). In principle, losses arising from such actions are the responsibility of the company as a legal entity under the doctrines of separate legal entity and limited liability. However, where such losses result from the fault, negligence, abuse of authority, breach of fiduciary duty, or other unlawful acts committed by the board of directors, the board of commissioners, or controlling shareholders, the principle of limited liability may be set aside through the application of the piercing the corporate veil doctrine. Under such circumstances, corporate organs proven to have abused the corporate legal entity may be held personally liable in order to ensure legal protection, legal certainty, and justice for public shareholders.